Lecture notes for the course "Social and labour relations in the organisation of accounting activities" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
Lecture notes for the course includes the main issues related to the theory of social and labour relations from the point of view of organising accounting activities. The course is an elective course in the humanitarian and socio-economic training block taught to bachelors in their fourth year. It is intended to develop students' theoretical knowledge of the content of social and labour relations, the regulatory framework of social and labour relations in Ukraine, the principles on which social and labour relations are based, the structure and indicators of labour resources assessment.
Keywords: lecture notes; economic activity; finance; labour market; technological innovations; audit; management